PSV-B-25 Performance of sunflower protein meal and dried yeast as secondary protein sources in canine diets. (8th October 2021) - Brewer, Lauren; Panasevich, Matthew; Frantz, Nolan; Daristotle, Leighann
Abstract: The objectives of this study were to assess graded inclusions of sunflower protein meal (SPM; crude protein: 54%, crude fat: 11%, crude fiber: 4%) and dried yeast (DY; crude protein: 50%, crude fat: 3%, crude fiber: 2%) on nutrient digestibility, stool quality, and palatability in adult dogs. Both SPM and DY were included at 5% and 10% in replacement of pea protein in a high-protein, chicken-based canine diet to maintain equal macronutrient concentrations across all test diets (formulated to 35% crude protein, 15% crude fat, 3% crude fiber). The study was approved and followed by the facility's Institutional Animal Care and Use Committee. A standard 2-bowl palatability test over a 2-day period was executed with adult dogs (n = 30 each) to determine intake ratios (IR) between test diets (5% and 10% SPM or 5% and 10% DY), and test diets vs. control. Total tract nutrient digestibility was evaluated (n = 8 per diet) with 5 days of diet acclimation followed by 5 days of total fecal collection. Stool quality was evaluated on a 1–5 scale, where 1 = hard/formed and 5 = non-formed/diarrhea. All data were analyzed by ANOVA (SAS v9.4) and T-tests post-hoc (Minitab 18). With P < 0.05 considered statistically significant, no differences were observed between diets for protein digestibility (all >84% avg) or stool scores (all averages between 2.25–2.50). For DY-containing diets, no significant differences in IR were noted vs. control (IRs = 35:65, 5% DY vs control; 40:60, 10% DY vs. control). However, palatability of control was preferred vs. SPM-containing diets (P< 0.05; IRs = 19:81, 5% SPM vs. control; 29:71, 10% SPM vs. control). Overall, detriments in protein digestibility and stool quality were not evident with DY and SPM, suggesting their viability as alternative protein sources in dog diets.